Introducing an Innovative Tool for Enhanced Precision in Strabismus Surgery: The Suh Botulinum Toxin Forceps - Lu, Josephine; Yassin, Shaden H.; Rezaei, Kimia; Hong, John D.; Tsai, E-Jine; Mossadeghian, Tara; Kefalov, Yan; Shahraki, Kourosh; Amin, Mateen; Suh, Donny W. (Korean journal of ophthalmology, 2025)
KCI Citation Count: 0